A Nanoporous Alumina Membrane Based Impedance Biosensor for Histamine Detection with Magnetic Nanoparticles Separation and Amplification. (2017) - Ye, W.W.; Ding, Y.T.; Sun, Y.; Tian, F.; Yang, M.
Abstract: Seafood, especially red fish is rich in histidine, which is essential for infants and adults. With fish freshness decline or spoilage, enzyme catalysis or microorganisms cause decarbonylation of histidine to form histamine, which threatens human body by dietary and affects allergic and inflammatory reaction. Current histamine assay needs complex operation, numerous steps, and time-consuming. In this study, a functionalized nanoporous alumina membrane was used to construct a rapid and highly sensitive impedance biosensor with magnetic nanoparticles (MNPs) for target molecule pre-concentration and separation. When the functionalized MNPs accumulated histamine, they were separated by magnetism from samples and added to the anti-histamine antibody modified nanoporous alumina membrane causing blocking effect in the nanopores by immune reaction. Impedance increased as histamine concentrations increased from 1 μM to 40 mM. The limit of detection was as low as several micromolar. The biosensor provides a novel, highly sensitive and specific sensing mechanism and constructs a new technology and method for justifying seafood freshness to prevent toxic reaction in human body. It is a new approach for food quality safety control.